The Influence of Barangay Officer in Enhancing Public Safety on Barangay Batasan Hills Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Background of the Study Barangay is a place where you would know about issues,information, and the like regarding its constituents. The Barangay Batasan is in charge oforganizing development projects and programs within its boundaries, carrying out policies andactivities in the community, and providing the inhabitants with basic services that barangayofficials, personnel, and members of the Lupong Tagapamayapa and staff are expected tocarry out their prescribed obligations and responsibilities at the local level by upholding thelaws, executing pertinent initiatives, and advancing the welfare of all.Barangay Officials in implementing ordinances and administrative code of the barangay(3.59), follow the instruction order to ensure the safety of the people in their barangay and thebarangay responds immediately when called for help (3.57), help the Barangay Officialsprevent crimes and promote peace and order (3.54), conducts planning and strategicalmethod to promote public safety (3.52), and initiates teamwork in preventing or otherwiseminimizing the commission of crime in the barangay (3.49).
Keywords: Criminology